The most important problems facing the agricultural workforce in Basra Governorate - Habeeb Azal , Balqis; Hamid Majid , Assist. Prof. Dr.Osama (Basra studies journal, 2023)
The importance of detecting and diagnosing the problems faced by workers in the agricultural sector of the economically active population is to work on providing all means to eliminate those obstacles that affect the efficiency of workers’ performance and their role in the production process. The study area based on the official data related to the topic of the research as well as the results of field work for the year 2020, and the research adopted the descriptive analytical approach and the quantitative method in presenting and discussing the research vocabulary. The study concluded many results, the most prominent of which was the lack of government support, represented by the weak role of the agricultural policy followed, as the problem of the low financial return of the farmer reached (41.8%) of the problems of reluctance to agricultural work, while the decrease in the worker’s share of agricultural land reached (0.1) dunums for the agricultural worker, and the continuation of the trespassing and bulldozing of agricultural lands. In order to eliminate or mitigate these problems, a methodology and action plans should be developed that develop the capabilities of the farmer and the farmer himself, support his productive projects, and protect his agricultural production and quality by establishing a marketing price policy to protect the local product and avoid damages that may affect farmers, and activate laws that limit commercial speculation. Which victimizes both the agricultural producer and the consumer.